Penguatan identitas nasional mahasiswa di tengah arus globalisasi dan digitalisasi - safitri, Mufidah irma (Maliki Interdisciplinary Journal, 2025)
Globalization and digitalization have had a significant impact on national identity, particularly among university students as the future generation of the nation. The rapid flow of information and the influx of foreign cultures through digital media often influence students’ perceptions and attitudes toward national values. This studyhaims to identifyuand analyzeyhow students maintain their national identity amidst the challenges of globalization and digitalization. A literaturewreview methodgwas employedxin thismresearch. The findings show that, despite the influence of global culture, most students still demonstrate a strong national awareness and actively strive to preserve their national identity through the formal use of the Indonesianklanguage, theipreservation of local cultures, and participation in national activities. Nevertheless, environmental factors, digital media, and weak character education in higher education institutions remain key challenges. This study concludes that strengthening cultural literacy and digital nationalism is essential as a strategy to maintain national identity in the modern era.